2020
DOI: 10.1155/2020/8583543
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Application of Novel Ferric Oxide-Amine Material for Removal of Nitrate and Phosphate in Water

Abstract: Ferric oxide-amine material was synthesized and applied as a novel adsorbent for nitrate and phosphate removal from aqueous solution. The properties of ferric oxide-amine were examined using TGA, FTIR, BET, SEM, EDX, SEM-mapping, and XRD analysis. The results showed that the adsorption using ferric oxide-amine material reached equilibrium after 30 and 60 min for nitrate and phosphate, respectively. The highest nitrate and phosphate adsorption capacities were 131.4 mg nitrate/g at pH 5-6 and 42.1 mg phosphate/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…However, the adsorption capacity decreases with the larger adsorbent amount since the Cd distributed on the surface of each adsorbent unit decreases. This is consistent with previous studies on the influence of adsorbent mass on the efficiency and adsorption capacity of the material [12,19]. In this study, the mass of 50 mg of material in 50 mL of 10 mg/L Cd solution gave a Cd adsorption efficiency of 99.97%, an adsorption capacity of 9.97 mg/g, and a Cd concentration after treatment of 0.029 mg/L.…”
Section: Batch Adsorption Of Cadmiumsupporting
confidence: 92%
“…However, the adsorption capacity decreases with the larger adsorbent amount since the Cd distributed on the surface of each adsorbent unit decreases. This is consistent with previous studies on the influence of adsorbent mass on the efficiency and adsorption capacity of the material [12,19]. In this study, the mass of 50 mg of material in 50 mL of 10 mg/L Cd solution gave a Cd adsorption efficiency of 99.97%, an adsorption capacity of 9.97 mg/g, and a Cd concentration after treatment of 0.029 mg/L.…”
Section: Batch Adsorption Of Cadmiumsupporting
confidence: 92%
“…The peaks at 1384 and 1468 cm −1 are the stretching vibrations of C=O [19]. The bands at 541 and 851 cm −1 were assigned to the stretching vibra-tion of Bi−O [24], while the wide band at 3442 cm −1 and peak at 1640 cm −1 are the stretching and deformation vibrations of OH − groups in physically absorbed water molecules [25]. Overall, the results showed that no impurities (e.g.…”
Section: Characterization Of Bi2o2co3mentioning
confidence: 75%